A manual for the 21st century art institution - Altshuler, Bruce; Sharmacharja, Shamita (London : Koenig Books ; London : Whitechapel Gallery, 2009)
- Reception / Iwona Blazwick##- Installations / Brian O'Doherty##- Collections / Bruce Altshuler##- Bookshop / Maria Fusco##- Exhibitions / Adam Szymczyk##- Archive / Nayia Yiakoumaki, Charles Merewether##- Gallery / Nayia Yiakoumaki##- Private museum / chris Dercon##- Cafe / Niru Ratnam##- Auditorium / Mark Nash##- Education tower / Caro Howell##- Skyline / sukhdev Sandhu.
CCS Gent
"A room by room guide to the contemporary institution of the future, this collection of new essays considers the evolution of gallery and museum practice."
boek